Doing More with a DM: A Survey on Library Social Media Engagement - Wardell, Jason; Kelly, Katy (Evidence Based Library and Information Practice, 2022)
Objectives – This study sought to determine the role social media plays in shaping library services and spaces, and how queries are received, responded to, and tracked differently by different types of libraries.Methods – In April and May of 2021, researchers conducted a nine-question survey (Appendix A) targeted to social media managers across various types of libraries in the United States, soliciting a mix of quantitative and qualitative results on prevalence of social media interactions, perceived changes to services and spaces as a result of those interactions, and how social media messaging fits within the library’s question reporting or tracking workflow. The researchers then extracted a set of thematic codes from the qualitative data to perform further statistical analysis.Results – The survey received 805 responses in total, with response rates varying from question to question. Of these, 362reported receiving a question or suggestion via social media at least once per month, with 247 reporting a frequency of less than once per month. Respondents expressed a wide range of changes to their library services or spaces as a result, including themes of clarification, marketing, reach, restriction, collections, access, service, policy, and collaboration. Responses were garnered from all types of libraries, with public and academic libraries representing the majority.Conclusion – While there remains a disparity in how different types of libraries utilize social media for soliciting questions and suggestions on library services and spaces, those libraries that participate in the social media conversation are using it as a resource to learn more from their patrons and communities and ultimately are better situated to serve their population.